Asteroseismic inferences from the study of non-linearities in δ Sct stars - Lares-Martiz, Mariel (Frontiers in Astronomy and Space Sciences, 2022)
Many pulsating star light curves must be interpreted strictly in the framework of a non-linear theory. Detection of non-linear interactions between pulsation modes has increased due to the ultra-precise photometric data provided by space missions. That is why it is now possible and essential to continue the effort of building data-driven non-linear pulsation models. The analysis of non-linear stellar light curves has become a fundamental challenge of asteroseismology in the era of space missions. In this paper, a diagnostic method is presented. It is based on an observational characterisation of the non-linear behaviour of High-Amplitude Delta Scuti (HADS) stars. It diagnoses the nature of non-linear pulsations in $δ$ Sct stars of lower amplitudes. It potentially provides an extra hint to identify a radial mode and determine its radial order $n$. Additionally, it might show signatures of moderate to fast rotation in these stars. Overall, this paper shows the capabilities for making such asteroseismic inferences from studying combination frequencies in $δ$ Sct stars.